1999
DOI: 10.1111/j.1600-0773.1999.tb00891.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tobramycin Nephrotoxicity in Young Adult and Aged Female Rats

Abstract: Abstract; A two week toxicity study was performed in rats to study the possible age-dependent toxicity of tobramycin, an aminoglycoside antibiotic with well known ototoxic and nephrotoxic properties in animals and man. Young adult female WagiRij rats aged 12 weeks (n=10) and old female rats aged 23 to 26 months (n=14) were treated subcutaneously with 0, 10, 40 or 160 mg tobramycin sulphate/kg/day. Clinical chemistry and urinalysis revealed significant changes in renal function in young adult rats mainly at 160… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…However, as Ward et al (23), we do not retrieve such an association with HS, though the disease is often widespread in our 41 mice. In addition, the signification of the frequency of renal hyaline droplets in our control group remains elusive, as such droplets are otherwise mentioned only in nephrotoxicity studies (15,17,24).…”
Section: Discussionmentioning
confidence: 98%
“…However, as Ward et al (23), we do not retrieve such an association with HS, though the disease is often widespread in our 41 mice. In addition, the signification of the frequency of renal hyaline droplets in our control group remains elusive, as such droplets are otherwise mentioned only in nephrotoxicity studies (15,17,24).…”
Section: Discussionmentioning
confidence: 98%
“…These ex vivo studies again demonstrated that the proximal tubular epithelial cells had an inherent increase in susceptibility to injury. Aged Wag/Rij rats (23–26 months) are more sensitive to tobramycin, an aminoglycoside antibiotic, as evidenced by tubular necrosis and urinary NAG levels [ 45 ]. More recent studies have extended age-dependent AKI models to the mouse.…”
Section: Aging and Aki: Experimental Modelsmentioning
confidence: 99%
“…The duration of aminoglycoside therapy, with a cut‐off point at 6 or 7 days, and the cumulative dose are recognized in both uni‐ and multivariate analysis as strong and well documented toxicity factors even if individualized pharmacokinetic monitoring is used [10–22]. High serum peak concentrations in the very elderly population, and administration of aminoglycosides during patients' rest periods, may also favor nephrotoxicity [23–25].…”
mentioning
confidence: 99%